2006
DOI: 10.4103/0253-7613.27024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immunomodulatory activity of the methanol extract ofFicus benghalensisroots in rats

Abstract: Objective: To evaluate the immunomodulatory activity of the aerial roots of Ficus benghalensis (Family Moraceae). Materials and Methods: Various extracts of the aerial roots of Ficus benghalensis were evaluated for potential immunomodulatory activity, using the in vitro polymorphonuclear leucocyte (human neutrophils) function test. The methanol extract was evaluated for immunomodulatory activity in in vivo studies, using rats as the animal model. The extracts were tested for hypersensitivity and hemagglutinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 2 publications
0
39
0
Order By: Relevance
“…The plates were incubated in carbon dioxide (CO 2 ) incubator for one hour at 37 °C. They were allowed to settle at room temperature for 60 min until the plates showed a small button formation (negative pattern) [9]. Positive haemagglutination result was determined by the appearance of diffused color and absence of button shape formation at the bottom of well.…”
Section: Determination Of Haemagglutination Antibody (Ha)mentioning
confidence: 99%
“…The plates were incubated in carbon dioxide (CO 2 ) incubator for one hour at 37 °C. They were allowed to settle at room temperature for 60 min until the plates showed a small button formation (negative pattern) [9]. Positive haemagglutination result was determined by the appearance of diffused color and absence of button shape formation at the bottom of well.…”
Section: Determination Of Haemagglutination Antibody (Ha)mentioning
confidence: 99%
“…It is locally known as Bot (Bangladesh), Bargad (India), Gotu Nuga (Sri Lanka), and belongs to the family Moraceae. Although there was immunomodulatory activity demonstrated using a methanol extract of F. benghalensis roots in an animal model 57 , only an in vitro study exists in support of its anti-tumor activity of this plant. Hawary et al 58 reported the methanol extract of F. benghalensis as a weak anti-tumor agent against HepG2 and MCF-7 tumor cell lines at a lower extant.…”
Section: Ficus Benghalensis Lmentioning
confidence: 99%
“…F. benghalensis is traditionally used as astringent, depurative, anti-inflammatory, ophthalmic, stypic, antiarthritic, diaphoretic, antidiarrhoeic, and antihelmenthic [26]. This was also the reason for choosing these two plants in this preliminary study.…”
Section: Discussionmentioning
confidence: 99%